IMPLEMENTASI KEBIJAKAN KEMENPORA DALAM PEMBINAAN ATLET MENEMBAK PELATNAS MENUJU OLIMPIADE TOKYO 2020 - Paragra Duncan Sentausa; Tjitjik Rahaju (Universitas Negeri Surabaya, 2021)
Coaching athletes is one of the most important steps that must be achieved to realize the ideals of all countries, including Indonesia. This coaching is also part of efforts to create achievements of the Indonesian nation through various fields; including sports (Harahap, 2018). Efforts in fostering athletes continue to be improved by governments in any country. Harahap called this the Indonesian government's response to produce outstanding athletes referring to Law no. 3 of 2005 which is the basis. Through this coaching and development, it is hoped that it will ensure equal access to sports, health and fitness, performances, and manage sports that can facing the challengesanddemands of changing nationals and global’s life.Sports coaching is carried out by both the government and local governments. The coaching also includes for Education, Recreation and achievement. This article discusses the development of athletes, especially those carried out by the government to create achievements. As is known, sports achievement is something that is visible and measurable, meaning that sports coaching is carriedout with a scientificapproach starting fromtalent scouting tothe training process. Sports coaching and athlete development are inseparable parts. Especially in sports that are directed at achieving achievements.This research focuses on national athletes in the framework of coaching that aims to form talented Athletes and know how athletes shoot to the International Level who are prepared to compete in the prestigious Summer Olympics Tokyo, Japan 2021 and National Sports Week 2021 held in Papua. Keywords: Regulation Implementation, Athlete, Training, Olympic Pembinaan atlet merupakan salah satu langkah terpenting yang harus dicapai untuk mewujudkan cita-cita semua Negara, termasuk Indonesia. Pembinaan ini juga menjadi bagian dari upaya menciptakan prestasi bangsa Indonesia melalui berbagai bidang; termasuk Olah Raga. Upaya dalam membina atlet terus ditingkatkan oleh pemerintahan di negara manapun. Harahap menyebut ini sebagai respon pemerintah Indonesia untuk menghasilkan atlet-atlet berprestasi merujuk pada UU No . 3 tahun 2005 yang menjadi landasannya. Melalui pembinaandan pengembangan ini, kami memastikan ada pemerataan akses kepada olahraga, meningkatkan kesehatan dan kebugaran, meningkatkan kinerja, dan mengelola olahraga yang mungkin menghadapi tantangan dan tuntutan perubahan dalam kehidupan nasional dan global. Pembinaan olah raga dilakukan baik oleh pemerintah maupun pemerintah daerah. Pembinaan tersebut juga mencakup untuk pendidikan, rekreasi dan prestasi. Artikel ini membahas tentang pembinaan atlet terutama yang dilakukan pemerintah untuk menciptakan prestasi. Seperti yang diketahui Hasil olahraga jelas terutur. Singkatnya, pelatihan ola hraga dilakukan dengan pendekatan saintifik, mulai dari pencarian bakat hingga operasi pelatihannya. Olahraga dan pembinaan atlet menjadi bagian yang tidak bisa dipisahkan. Terlebih dalam cabang-cabang olah raga yang diarahkan agar dapat meraih prestasi. Penelitian ini juga berfokus pada atlet nasional dalam rangka pembinaan yang bertujuan untuk membentuk atlet berbakat dan mengetahui bagaimana perjalanan atlet menembak hingga sampai pada tingkatan internasional yang dipersiapkan untuk berkompetisi dalam ajang bergengsi Olimpiade Musim Panas 2020 dan Pekan Olahraga Nasional 2021 yang diselenggarakan di Papua. Kata Kunci: Implementasi Kebijakan, Atlet, Pembinaan, Olimpiade